Tax Consolidation Regime for Corporate Groups - BENOMAR, Touhami; SADDEK, Abdelkader; BENCHERIF, Slimane (Journal of Ecohumanism, 2025)
The Algerian legislator has granted companies that are members of a corporate group a set of tax privileges aimed at encouraging the formation of groups, which seek to protect member companies from external competition in domestic markets. However, these privileges are subject to strict conditions that have narrowed the concept of a corporate group in tax law compared to its definition in commercial law and competition law, thereby depriving the latter of the benefits of the tax consolidation regime.In contrast, these conditions are considerably more flexible in French legislation, with the objective of subjecting the largest possible number of corporate groups to the tax consolidation regime.